Resolving Spatial Conflicts In Computer-Generated Collision Diagrams For Road Accident Analysis - Mahmud, Ahmad Rodzi (2002)
This research deals with the depiction of road accident scenes using symbols. When cartographic symbols are presented, there may be situations where they are either too close or overlapping. Manual intervention is thus needed to rearrange the symbols to avoid confusing the user. This condition, known as spatial conflict, is part of the problem in cartography especially in the process of automated generalization. When a collision diagram is drawn to show the road user movements (RUM) that indicate the nature of vehicle maneuver in road accidents at a particular site, the position of the event is often re-Iocated because of the type and size of symbols used. The changes made are always tentative, iterative and subjective. It is also a time consuming process, as the draughtsman need to decide the right and accurate symbols to be presented. These processes are needed, as the symbols are usually close or overlapping against each other. The diagram may not be much helpful to the traffic engineer if no intervention is being made to re-position the symbols. A clear and informative diagram is necessary to determine the predominant type of road accident, and for proposing the best remedy. Therefore, the procedures in the creation of Collision Diagram involve an iteration process which are subjective due to an array of human factors involved in making decisions. As a result, inaccuracy occurs in presenting the right position and the right symbols. Hence this work focuses on the automation process for resolving the spatial conflict.